Hepatic Metabolomics Investigation in Acute and Chronic Murine Toxoplasmosis - Chen, Xiao-Qing; Elsheikha, Hany M.; Hu, Rui-Si; Hu, Gui-Xue; Guo, Shu-Ling; Zhou, Chun-Xue; Zhu, Xing-Quan (Frontiers in Cellular and Infection Microbiology, 2018)
Toxoplasma gondii poses a great threat to human health, with no approved vaccine available for the treatment of T. gondii infection. T. gondii infections are not limited to the brain, and may also affect other organs especially the liver. Identification of host liver molecules or pathways involved in T. gondii replication process may lead to the discovery of novel anti-T. gondii targets. Here, we analyzed the metabolic profile of the liver of mice on 11 and 30 days post infection (dpi) with type II T. gondii Pru strain. Global metabolomics using liquid chromatography-tandem mass spectrometry (LC-MS/MS) identified 389 significant metabolites from acutely infected mice; and 368 from chronically infected mice, when compared with control mice. Multivariate statistical analysis revealed distinct metabolic signatures from acutely infected, chronically infected and control mice. Infection influenced several metabolic processes, in particular those for lipids and amino acids. Metabolic pathways, such as steroid hormone biosynthesis, primary bile acid biosynthesis, bile secretion, and biosynthesis of unsaturated fatty acids were perturbed during the whole infection process, particularly during the acute stage of infection. The present results provide insight into hepatic metabolic changes that occur in BALB/c mice during acute and chronic T. gondii infection.